(untitled) (Review of Knowledge Economy, 2015)
The present study was carried out to investigate the effects of Punica granatum peel extracts and Ammi visnaga fruit extracts on the Acetylcholinesterase (AChE) activity in haemolymph and fat bodies of last instar nymphs and newly emerged adult females of Schistocerca gregaria. The extracts of both P. granatum peel and A. visnaga fruit predominantly enhanced the enzyme activity in haemolymph of nymphs and adults with few exceptions. The disturbance induced due to P. granatum peel extracts on AChE activity in fat bodies depended on both nymphal age and developmental stage. Where, although remarkable increase in AChE activity was detected in the mid- and late-aged nymphs, serious decrease was noticed in early-aged nymphs and adults. A. visnaga fruit extracts prohibited the early-aged nymphs to attain the normal enzyme activity in their fat bodies but promoted the nymphs of other ages to gain high activity. In fat bodies of adults, n-butanol extract of A. visnaga caused a pronounced inhibition of the enzyme activity but other extracts promoted for considerable increasing activity.